2010
DOI: 10.1118/1.3495541
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of the effects of anode surface roughness on x‐ray spectra

Abstract: The effects of anode surface roughness on x-ray spectra were successfully simulated by a Monte Carlo method. It was proved that the effect of the anode surface roughness could not be modeled by simple filters made from the anode material. The surface roughness (Ra) was found to be an inadequate quantity to describe the effect of anode surface roughness on x-ray spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Other authors found comparable results in the sense that increased tube aging rather manifests in decreasing x-ray output when investigating low α take off and high U tube than in changed HVL. 1,2,11 The roughness, that is, R a , might be a value that is easier and faster to obtain than a fully three-dimensional dataset of the surface. Figure 10 shows R measured plotted against the measured R a values.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other authors found comparable results in the sense that increased tube aging rather manifests in decreasing x-ray output when investigating low α take off and high U tube than in changed HVL. 1,2,11 The roughness, that is, R a , might be a value that is easier and faster to obtain than a fully three-dimensional dataset of the surface. Figure 10 shows R measured plotted against the measured R a values.…”
Section: Discussionmentioning
confidence: 99%
“…The surface roughness of recovered rotating anodes after failure rarely exceeds R a /S a = 10 µm or R z = 45 µm. 1,3,7,26 For example, the surfaces shown in Figs. 1(a) and 1(b) calculate to R a = 1.8 µm, R z = 15 µm and R a = 4.5 µm, R z = 32 µm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations